Student Attitude Towards English Language Learning in an Urban Senior High School in Batu: A Survey - Qimmahtum, Rohi; Fikri Fadhil Khairy, Muhammad; Swandari, Nila (KnE Social Sciences, 2023)
This study aimed to investigate urban students’ attitudes toward English learning. This study uses a quantitative method by giving an online questionnaire using Likert scales. The questionnaire focused on two aspects of attitude: BALLI by Hortwitz (1988) and Attitude towards English Language Learning by Sudirman and Huzairin (2017). 42 students from Islamic Senior High School in Batu, East Java, Indonesia were the participants of this study. The results of this study found that the students generally had a positive attitude toward English language learning. However, a unique pattern shows a duality where the students are anxious to speak English, but they also consider making mistakes as a part of learning. The students also felt that English is important to foster their interest in the language and encourage them to learn more. Keywords: Attitudes, Urban school, English language Learning